Integrating Oceanographic Data and Benthic Community Structure Temporal Series to Assess the Dynamics of a Marginal Reef - Biscaia Zamoner, Julia; Aued, Anaide Wrublevski; Macedo-Soares, Luis Carlos Pinto; Picolotto, Vitor André Passos; Eiras Garcia, Carlos Alberto; Segal, Bárbara (Frontiers in Marine Science, 2021)
Reefs are the richest marine ecosystems. Their benthic communities generate structural complexity and participate in nutrient cycles, providing habitat and food for many marine species. These ecosystems have been threatened by local and global anthropogenic impacts and changes in community structure have led to loss of biodiversity, ecosystem function and services worldwide. Most studies about these structural changes have been conducted in Caribbean and Indo-Pacific coral reefs. In the Southwestern Atlantic, where reefs are naturally algae-dominated, these efforts are incipient, especially at oceanic islands where local anthropic impacts tend to be lower, and natural and climate-induced fluctuations might be easily detected. We conducted the first temporal assessment of benthic communities and the influence of oceanographic parameters between 2013-2019 in Fernando de Noronha (FNA), the largest Brazilian oceanic archipelago. We annually sampled benthic communities in FNA’s shallow reefs (2-21m) using photoquadrats, quantified and gathered organisms in major groups according to their functional roles. We also characterized and tested ‘sea surface temperature’, ‘marine heatwaves’, ‘diffuse attenuation coefficient’ and ‘wave energy’ influence for the same period. The most abundant groups were epilithic algal matrix (EAM; mean annual coverage: 23-60%), macroalgae (15-35%) and calcifiers (15-29%), followed by cyanobacteria (1-37%), suspension/filter-feeders (<2%), zoanthids (<1%) and other invertebrates (<0.1%). EAM was negatively correlated with ‘marine heatwaves’ and positively correlated with ‘wave energy’, while macroalgae and calcifiers showed opposite responses to ‘marine heatwaves’ and ‘wave energy’, respectively. Cyanobacteria was positively correlated with ‘marine heatwaves’. The dominance of EAM and macroalgae was already described for reefs along the Brazilian Province and we demonstrated the persistence of this structure over the years in FNA, with exception of 2019 when there was a substantial increase of cyanobacteria after a strong marine heatwave. Our results suggest a flickering dynamic between EAM and macroalgae, which vary according to the oceanographic conditions, reinforcing its distinct dynamics from most tropical coral reefs. However, the increase of cyanobacteria added to projections of more frequent and stronger marine heatwaves worldwide indicate possible structural changes in this community. Continued monitoring of community and oceanographic drivers is key for better understanding and predicting changes in important marginal reefs.